Lifetime experiences of gender-based violence, depression and condom use among female sex workers in Cameroon. (September 2019) - Abelson, Anna; Lyons, Carrie; Decker, Michele; Ketende, Sosthenes; Mfochive Njindam, Iliassou; Fouda, Ghislaine; Ndonko, Flavien; Levitt, Daniel; Tamoufe, Ubald; Billong, Serge; Bissek, Anne-Cecile Zoung-Kanyi; Baral, Stefan D
Background: In general populations, consistent data highlight the relationships among violence, HIV risk behavior and depression; however, these patterns are not well understood among female sex workers (FSWs). We examined the relationship between FSWs' experiences with sexual violence and consistent condom use as a key HIV risk behavior and explored mental health as a potential mediator. Methods: In total, 2, 165 FSWs were recruited via respondent-driven sampling in Cameroon in 2016. The women answered questions about violence, condom use and mental health. Results: Inconsistent condom use with clients was reported by 23.5% of participants (508/2, 165). Lifetime sexual violence was prevalent with 33.0% (713/2, 163) of participants. Almost 50% (1, 067/2, 143) of respondents had some level of depression. Sexual violence was significantly associated with inconsistent condom use (adjusted risk ratio (aRR) 1.4, 95% confidence interval (CI) (1.2–1.6)). Of FSWs with no depression, 24.9% (267/1, 071) reported sexual violence, versus 56.1% (32/57) of respondents with severe depression ( p  < .01). Severe depression significantly increased risk of condomless sex (aRR 1.8, 95% CI (1.3–2.6)); in mediation analysis, both sexual violence and severe depression remained significant predictors of condomless sex (aRR 1.4, 95% CI (1.2, 1.6) and aRR 1.7, 95% CI (1.2–2.4), respectively). Depression did not mediate the relationship between sexual violence and condom use. Conclusion: Sexual violence and depression are prevalent and independently associated with condom nonuse with clients among FSWs in Cameroon. Results highlight the need for interventions to address mental health as well as gender-based violence for FSWs.